How Is Household Food Security Assessed In Small Island Communities? A Narrative Review - Dyah Ayu Suryaningrum; Shelly Sylvia Agustina; Daeva Mubarika Raisa; M. Alwi Shahab; Farah Ainun Jamil (Indonesian Journal of Innovation Multidisipliner Research, 2026)
Household food security assessment in small island communities requires indicators that reflect the specific realities of island life. Small islands often face limited land and freshwater resources, dependence on external food supply, high transport costs, climate vulnerability, and shifting dietary patterns. This article aims to review how household food security is assessed in small island communities and to identify key indicators commonly used in the literature. Using a narrative review of Scopus-indexed publications, this study synthesizes indicators across four dimensions of food security: availability, access, utilization, and stability. The review shows that common indicators include local food production, fisheries resources, food import dependency, household income, food expenditure, dietary diversity, nutrition outcomes, climate shocks, and supply chain disruption. However, conventional assessments often overlook island-specific indicators such as dependence on mainland supply, sea transport access, food sharing, social networks, marine livelihood dependence, dietary transition, and freshwater constraints. The study suggests that household food security assessment in small islands should combine standard food security indicators with contextual indicators that capture geographic isolation, environmental uncertainty, and community-based coping mechanisms. Such an approach can support more accurate evidence and context-sensitive policy interventions for small island food systems.